The Deletion of Endothelial Sodium Channel α (αENaC) Impairs Endothelium-Dependent Vasodilation and Endothelial Barrier Integrity in Endotoxemia in Vivo - Sternak, Magdalena; Bar, Anna; Adamski, Mateusz G.; Mohaissen, Tasnim; Marczyk, Brygida; Kieronska, Anna; Stojak, Marta; Kus, Kamil; Tarjus, Antoine; Jaisser, Frederic; Chlopicki, Stefan (Frontiers in Pharmacology, 2018)
The role of epithelial sodium channel (ENaC) activity in the regulation of endothelial function is not clear. Here, we analyze the role of ENaC in the regulation of endothelium-dependent vasodilation and endothelial permeability in vivo in mice with conditional αENaC subunit gene inactivation in the endothelium (endo-αENaCKO mice) using unique MRI-based analysis of acetylcholine-, flow-mediated dilation and vascular permeability. Mice were challenged or not with lipopolysaccharide (LPS, from Salmonella typhosa, 10 mg/kg, i.p.). In addition, changes in vascular permeability in ex vivo organs were analyzed by Evans Blue assay, while changes in vascular permeability in perfused mesenteric artery were determined by a FITC-dextran-based assay. In basal conditions, Ach-induced response was completely lost, flow-induced vasodilation was inhibited approximately by half but endothelial permeability was not changed in endo-αENaCKO vs. control mice. In LPS-treated mice, both Ach- and flow-induced vasodilation was more severely impaired in endo-αENaCKO vs. control mice. There was also a dramatic increase in permeability in lungs, brain and isolated vessels as evidenced by in vivo and ex vivo analysis in endotoxemic endo-αENaCKO vs. control mice. The impaired endothelial function in endotoxemia in endo-αENaCKO was associated with a decrease of lectin and CD31 endothelial staining in the lung as compared with control mice. In conclusion, the activity of endothelial ENaC in vivo contributes to endothelial-dependent vasodilation in the physiological conditions and the preservation of endothelial barrier integrity in endotoxemia.